A New Illusion at Your Elbow. (February 2015) - Brugger, Peter; Meier, Rebekka
On experiencing distal-proximal tactile motion on the volar side of the forearm starting at the wrist, subjects significantly anticipate touch of the elbow crook. This illusion, popular as a children's game, was quantified in ninety participants (forty-seven women) on both arms. As a top-down explanation of the illusion, we discuss a model of Bayesian inferences. As a bottom-up contribution, we consider afterdischarges of cortical neurons, which receive input from skin mechanoreceptors specifically driven by slow-motion tactile stimuli. Like previously described illusions, the elbow crook illusion is larger on the nondominant arm. Women showed a smaller illusion than men, giving testimony to their reportedly superior cutaneous sensitivity.